Greece : Preliminary Debt Sustainability Analysis-Updated Estimates and Further Considerations. (IMF Staff Country Reports; Country Report ;, 2016)
This paper provides preliminary debt sustainability analysis (DSA) of Greece. Debt was deemed sustainable, but not with high probability, when the first program was adopted in May 2010. The much deeper-than-expected recession necessitated significant debt relief in 2011-12 to maintain the prospect of restoring sustainability. Serious implementation problems caused a sharp deterioration in sustainability, raising fresh doubts about the realism of policy assumptions, especially from mid-2014. Developments since last summer suggest that a realignment of critical policy, and DSA assumptions can no longer be deferred if the DSA is to remain credible. Staff believes that revised program targets remain sufficiently ambitious to warrant continued support from Greece's European partners.